The relationship between strategic management and technology adoption: a review and bibliometric analysis - Sukma Warta; Suddin Lada; Brahim Chekima; Rudy Ansar; Arif Kamisan Pusiran (Penerbit UMS, 2022)
This research has been conducted and is directed toward a systematic literature review and bibliometric visualization analysis of the relationship between the strategic management model and technology adoption. This research aims to document the intellectual structure, volume, and knowledge-development directions empirically. To achieve this objective, we will use Scopus to access the databases, VOS Viewer and Excel to analyze data. From the analysis that has been conducted, we have identified that there is a difference in the volume of the articles that have been produced on strategic management and technology adoption published in the current ten years, which are from 2013 until 2022, by comparing to the entire period before 2013 which is from 2003 until 2012 with 346 documents articles that have been published in the last ten years. Furthermore, the bibliometric analysis that will be conducted in this research by using the platform that has been chosen will identify the most influential journals, authors, and papers in this study field that have been chosen which are strategic management and technology adoption.